Toward a Practical Technique to Halt Multiple Virus Outbreaks on Computer Networks - Hole, Kjell Jørgen (Journal of Computer Networks and Communications, 2012)
The author analyzes a technique to prevent multiple simultaneous virus epidemics on any vulnerable computer network with inhomogeneous topology. The technique immunizes a small fraction of the computers and utilizes diverse software platforms to halt the virus outbreaks. The halting technique is of practical interest since a network's detailed topology need not be known.